Baroclinic Residual Circulation and Mass Transport Due to Internal Tides. Issue 4 (2nd April 2020) - Masunaga, Eiji; Arthur, Robert S.; Yamazaki, Hidekatsu
Abstract: Baroclinic (BC) tidal residual circulation due to internal tides is investigated around islands over a shallow ridge using a numerical ocean model. Internal tides enhance vertical mixing over shallow slopes, leading to horizontal density gradients that drive BC residual circulation along the main thermocline. For a strongly stratified summer case, the vertical diffusivity estimated by the Mellor and Yamada turbulence closure model exceeds 1 × 10 −2  m 2  s −1, and the velocity of BC residual circulations reaches 0.2 m s −1 . The magnitude of BC residual circulation is larger than that of barotropic residual tidal circulation, implying that BC residual circulation due to internal tides plays an important role in coastal ocean circulation. Furthermore, BC residual flow accounts for an equal percentage (5%) of the total tidal kinetic energy as the barotropic residual flow under summer stratification conditions. Results from a coupled sediment resuspension and transport model show the growth of intermediate nepheloid layers formed by strong bottom shear stress and BC residual flow. The residual component contributes largely (23% of the total in summer) to the total suspended sediment flux. Seasonal variability is explored, with weaker winter stratification leading to reduced mixing, and thus weaker BC residual circulation and sediment flux. The magnitude of the BC residual circulation is also shown to be proportional to the square of the tidal amplitude. Plain Language Summary: Through the transport and mixing of heat, nutrients, and sediment, ocean flows affect marine ecosystems as well as the global climate. However, because they are both inherently complex and difficult to model or observe, ocean transport and mixing processes are not fully understood. This study uses a numerical model to examine transport by internal tides, focusing on coastal regions where transport processes are especially important for marine ecosystems. Internal tides are tidal‐scale internal waves (with semidiurnal or diurnal period) that propagate in regions with density stratification, and are usually generated by tidal flow over topography. Model results show that as internal waves interact with the coastal slope, a time‐averaged residual flow develops with a maximum velocity near the main thermocline. This circulation, known as "baroclinic residual circulation, " is generated by mixing associated with internal tides and contributes to cross‐shore flows. Furthermore, by coupling a sediment resuspension and transport model to the internal tide simulation, it is shown that residual circulation transports sediment offshore, forming subsurface turbidity layers known as "intermediate nepheloid layers." These results imply that baroclinic residual circulation due to internal tides is an important contributor to cross‐shore transport in coastal ecosystems. Key Points: Spatially variable mixing due to internal tides drives baroclinic residual circulation along the thermocline in the coastal ocean Baroclinic residual circulation represents a significant portion of the kinetic energy budget where strong internal tides exist Baroclinic residual circulation contributes to suspended sediment transport, leading to the formation of intermediate nepheloid layers